Landscape history discoveries in the North West : proceedings of a conference sponsored by English heritage to celebrate the 25th anniversary of the Chester Society for landscape history, September 2011 - Varey, Sharon M.; White, G. J. (Graeme J.); Evans, Dai Morgan (University of Chester Press, 2012)
From optical remote-sensing technology (lidar) to more traditional forms of landscape analysis and documentary research, this volume brings together the work of both amateur and professional historians and archaeologists, united in their enthusiasm for the landscape of north-west England and north-east Wales. This collection of research papers arose from the Chester Society for Landscape History's 25th anniversary conference and includes a wealth of illustrations. The publication offers new insights into a wide range of features indicative of the region's history between the twelfth and the tw.